Malignant melanoma mimic fungal infection a case report - Juan Sun; Yun-Zhu Zhu; Pan-Pan Shao; Jing Ke; Wei Wang; Qiu-Lin Sun; Jia-Bin Li; Jun Cheng (BMC, 2022)
Abstract Background Most of malignant melanomas originate from skin and often metastasize to the lungs, rarely metastasizes to the liver and bone. However, imageology characters of lung metastasis tumor are commonly similar to those of fungal infections. Case presentation A patient was admitted with unhealed plantar puncture wound for 3 years, and cough and expectoration for 2 years. The chest computed tomography (CT) revealed multiple nodules with cavities, and the patient was diagnosed of pulmonary fungal infection in another hospital and received antifungal therapy for more than 8 months, but the clinical symptoms and chest imaging findings continue to progress. After admission, the pathological results of both lung biopsy and biopsy of the plantar wound 3 years ago indicated malignant melanoma. Conclusions The diagnosis of lung lesions cannot rely solely on imaging diagnosis, lung biopsy should be performed if necessary.